Circulating follicular helper T cells are increased in systemic sclerosis and promote plasmablast differentiation through the IL-21 pathway which can be inhibited by ruxolitinib. Issue 4 (11th April 2019) - Ricard, Laure; Jachiet, Vincent; Malard, Florent; Ye, Yishan; Stocker, Nicolas; Rivière, Sébastien; Senet, Patricia; Monfort, Jean-Benoit; Fain, Olivier; Mohty, Mohamad; Gaugler, Béatrice; Mekinian, Arsène
Abstract : Objectives: Systemic sclerosis (SSc) is an autoimmune disease characterised by widespread fibrosis, microangiopathy and autoantibodies. Follicular helper T (Tfh) cells CD4 + CXCR5 + PD-1 + cooperate with B lymphocytes to induce the differentiation of plasmocytes secreting immunoglobulins (Ig). Circulating Tfh (cTfh) cells are increased in several autoimmune diseases. However, there are no data about cTfh cells and their interaction with B cells in SSc. The aim of this study was to perform a quantitative and functional analysis of cTfh cells in SSc. Methods: Using flow cytometry, we analysed cTfh cells from 50 patients with SSc and 32 healthy controls (HC). In vitro coculture experiments of sorted cTfh and B cells were performed for functional analysis. IgG and IgM production were measured by ELISA. Results: We observed that cTfh cell numbers are increased in patients with SSc compared with HC. Furthermore, the increase in cTfh cells was more potent in patients with severe forms of SSc such as diffuse SSc and in the presence of arterial pulmonary hypertension. cTfh cells from patients with SSc present an activated Tfh phenotype, with high expression of BCL-6, increased capacity to produce IL-21 in comparison with healthy controls. In vitro, cTfh cells from patients with SSc had higher capacity to stimulate the differentiation of CD19 + CD27 + CD38 hi B cells and their secretion of IgG and IgM through the IL-21 pathway than Tfh cells from healthy controls. Blocking IL-21R or using the JAK1/2 inhibitor ruxolitinib reduced the Tfh cells' capacity to stimulate the plasmablasts and decreased the Ig production. Conclusions: Circulating Tfh cells are increased in SSc and correlate with SSc severity. The IL-21 pathway or JAK1/2 blockade by ruxolitinib could be a promising strategy in the treatment of SSc.